2011
DOI: 10.1177/1077546311410763
|View full text |Cite
|
Sign up to set email alerts
|

Time-delay feedback control of lathe cutting tools

Abstract: For some machining operations, tool vibrations decay with time, the trivial solution is a stable equilibrium solution, and hence the machined surface is smooth. For other operating conditions, the trivial solution is unstable and the tool undergoes large oscillations called chatter, which might be periodic, quasiperiodic, or chaotic, and hence the surface finish will not be smooth. Therefore, chatter must be avoided or mitigated to maintain machining tolerances, preserve surface finish, and prevent tool breaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Rezaie and Jahed Motlagh (2011) addressed a new adaptive delayed displacement feedback controller to stabilize a class of chaotic time-delayed systems with a variable parameter. Nayfeh and Nayfeh (2012) proposed a delayed acceleration feedback control strategy to mitigate regenerative chatter in turning on lathes. Recently, by the application of the finite difference technique combined with Floquet theory, Masri et al.…”
Section: Introductionmentioning
confidence: 99%
“…Rezaie and Jahed Motlagh (2011) addressed a new adaptive delayed displacement feedback controller to stabilize a class of chaotic time-delayed systems with a variable parameter. Nayfeh and Nayfeh (2012) proposed a delayed acceleration feedback control strategy to mitigate regenerative chatter in turning on lathes. Recently, by the application of the finite difference technique combined with Floquet theory, Masri et al.…”
Section: Introductionmentioning
confidence: 99%
“…After the signals are transferred to a computer, the control force κðy 3 ðτÞÀy 4 ðτÞÞ 3 is calculated. Then this force is applied on the wheel holder by an actuator, such as a piezoelectric stack, a magnetostrictive, or an electrostrictive actuator [40].…”
Section: Bifurcation Controlmentioning
confidence: 99%
“…As seen in Eq. (23), the bifurcation control can be realized by a close loop control strategy [1,40]. Specifically, the wheel and workpiece velocities (y 3 ðτÞ and y 4 ðτÞ) at the contact point are recorded by a laser velocimeter.…”
Section: Bifurcation Controlmentioning
confidence: 99%
“…They concluded that the damping ratio of the cutting tool increased about four times. Researchers (Al-Regib et al, 2003;Ding et al, 2020;Fallah and Moetakef-Imani, 2019;Insperger and Stepan, 2004;Kovacic, 1998;Khasawneh and Munch, 2016;Liu et al, 2016;Long and Balachandran, 2017;Moradi et al, 2009;Nayfeh and Nayfeh, 2011;Siddhpura et al, 2017) studied the control strategy for chatter suppression in cutting process. In view of this, they were successful in deriving an effective control law that suppresses chatter and finally helps in providing stability in the machining process by adjusting the amplitude and frequency of spindle speed variation.…”
Section: Introductionmentioning
confidence: 99%